Embracing Harmonizing Time: A Tafsir Perspective on Islamic Calendar Unification - Putra, Sudarmadi (UIN Sunan Gunung Djati Bandung, 2025)
The unification of the Islamic calendar is an important issue in bridging differences in calendars in various Muslim countries. This article examines the unification of the calendar from the perspective of Qur'anic exegesis, with a focus on verses relating to the determination of time, months, and astronomical signs. This analysis uses a thematic interpretation approach (tafsīr maudū‘ī) to identify the theological and methodological foundations in supporting the harmonization of the global Islamic calendar. The results of the study show that there is legitimacy in the Al-Qur'an to build a calendar agreement based on sharia principles and modern astronomy. This article offers an academic contribution to cross-national dialogue on the issue of the Islamic calendar.